Development of a Humidity Sensor Element Based on Sputter-deposited thin ZnO-Layers. (2016) - Klaas, D.; Rein, M.; Wurz, M.C.; Rissing, L.
Abstract: A sensor concept for humidity measurement has been invented at the Institute of Micro Production Technology. The sensor element is manufactured on silicon oxide wafers with respect to the requirements of a new direct deposition process. This new process allows for thinner sensors with higher measuring accuracy. High purity 4N zinc oxide is used for the humidity sensing layer. Sensor properties and characteristics have been evaluated using X-ray diffraction and scanning electron microscopy. Finally, the evaluation electronic concept based on an embedded system with a field programmable gate array (FPGA) is presented.